FRI0047 Prediction of Remission by Patients and Physicians: Does the Doctor Know Best?. (10th June 2014) - Bensen, W.G.; Haraoui, B.; Thorne, C.; Keystone, E.; Zummer, M.; Fortin, I.; Faraawi, R.; Chow, A.; Arendse, R.; Baker, M.; Jones, N.; Rampakakis, E.; et al.
Abstract : Background: Patient (PtGA) and physician (MDGA) assessment of global disease activity have been used as outcome measures individually or as part of composite scores in the measurement of rheumatoid arthritis (RA) disease severity and the evaluation of treatment effectiveness. However, discordance between the two is common 1 . The question arising is which global measure is a more valid predictor of disease remission. Objectives: The aim of the analysis was to compare PtGA and MDGA with respect to their association with remission based on DAS-28, SDAI and CDAI, using a sequential cross-sectional analysis. Methods: BioTRAC is an ongoing, prospective registry of patients initiating treatment for RA, ankylosing spondylitis (AS), or psoriatic arthritis (PsA) with infliximab (IFX) or golimumab as first biologics or after having been treated with a biologic for <6 months. Eligible patients for this study included RA patients treated with IFX who were enrolled between 2002 and 2012 with available information on 6-, 12-, or 18-month remission. Logistic regression analysis with the parametric Wald statistic was used to compare the independent association of MDGA and PtGA with remission at 6, 12 and 18 months. The WALD statistic assesses the extent of contribution of an individual predictor to an outcome of interest and can be used to compare the contribution of different predictors. Results: A total of 657 patients were included with mean (SD) age of 56.2 (13.5) years and disease duration of 10.1 (10.0) years. Significant (P<0.001) associations were observed between both PtGA and MDGA and achievement of remission at the corresponding assessments regardless of remission type. For DAS28 remission, the Wald statistic at 6, 12 and 18 months for MDGA vs. PtGA was 26.9 vs. 39.2, 12.7 vs. 35.9, and 19.8 vs. 22.5, respectively. For SDAI remission the MDGA and PtGA Wald statistics were 27.7 vs. 24.5, 27.8 vs. 28.5, and 32.4 vs. 23.4, respectively, at 6, 12 and 18 months. For CDAI remission, the Wald statistic for MDGA vs. PtGA at these time points was 34.8 vs. 26.9, 38.1 vs. 37.2, and 39.5 vs. 27.1. Similar results were obtained for predicting low disease activity. Conclusions: The results of this analysis show that PtGA is a better predictor of DAS28 disease remission compared to MDGA. This could be explained by the fact that DAS28 includes PtGA and not MDGA. However, for CDAI and SDAI, physicians were better in predicting remission although the superiority of the MDGA was not consistent over time. References: Bensen WG et al. Identification of Four Parameters that Drive the Discordance Between the Patient and Physician Global Assessment in Rheumatoid Arthritis. Canadian Rheumatology Association Annual Scientific Meeting, 2013, Ottawa, ON, Canada. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4276